Prevalence of Dietary Supplements Use among Gymnasium Users - Ayman H. Jawadi; Abdulmalik M. Addar; Abdulaziz S. Alazzam; Fahad O. Alrabieah; Abdullah S. Al Alsheikh; Roaa R. Amer; Al Anoud S. Aldrees; Maha A. Al Turki; Ali K. Osman; Motasim Badri (Journal of Nutrition and Metabolism)
Background. Several studies showed that regular gymnasium users use various dietary supplements without comprehension of their potential risks. Objective. To determine the prevalence and dietary supplement intake and assess the awareness of supplement use among regular gymnasium users in Riyadh, Saudi Arabia. Methods. A descriptive cross-sectional study was conducted among regular gymnasium users in Riyadh, Saudi Arabia, between April 2015 and June 2015. A validated structured questionnaire was used. Results. The study included 299 participants. Of these 113 (37.8%) were dietary supplements users and this was more common among males than females (44.7% versus 16.4%). Gender based analysis showed that males were exercising more frequently than females and the type of cardiovascular exercise was more among them. The most commonly used supplements were whey protein (22.1%), amino acids (16.8%), multivitamins (16.8%), creatine (11.5%), and omega 3 (11.5%). The reasons for taking dietary supplements were to improve body shape (47.7%), increase health (44.2%), and improve performance (41.5%). Conclusion. Most of the information about supplements was obtained from unreliable sources. More studies are needed to better understand supplements use and their impact on health in Saudi Arabia.